ANCANGAN MODEL PEMBELAJARAN MUATAN LOKAL BERBASIS BUDAYA KULINER - Rahmaniar Rahmaniar (Universitas Hasanuddin, 2020)
The study, entitled The Culinary Culture-Based Local Content Learning Model (MPMLBBK) is a study that refers to the Humanistic theory in the psycholinguistics of language learning. This model emphasizes the importance of human or student feelings (sipakatau concept), both in the mindset, feelings and behavior of students in decision making, as well as providing opportunities to actualize themselves to make learning meaningful so that in the future students can be useful in the midst of society. This study aims to describe the appropriate approach to learning models in teaching local content, especially the Bugis regional language in a fun, creative and innovative manner based on the traditional culinary culture of the Bugis people.